The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s1516-80342007000200006
|View full text |Cite
|
Sign up to set email alerts
|

Processo de implantação de Programa de Saúde Auditiva em duas maternidades públicas

Abstract: OBJETIVOS: Apresentar os resultados do processo de implantação de um programa de saúde auditiva neonatal em serviço público e revisar os aspectos determinantes no planejamento, efetividade, manutenção e aprimoramento. MÉTODOS: A fim de colaborar com a implantação de novos serviços, avaliamos os fatores: capacitação de equipe, ambiente de teste (ruído e indivíduo), falso-negativo, evasão e tempo de exame, em um estudo transversal, que incluiu a triagem auditiva de todos os recém-nascidos de duas maternidades pú… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
37
1
26

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 19 publications
10
37
1
26
Order By: Relevance
“…Results show that the average age of suspicion, the first appointment with physician, diagnostic, intervention and adaptation of hearing aid occurred later than in other researches or standards determined by national and international committees, which recommend that the diagnosis occurs around the 3 rd and 4 th month of a baby's life, and the intervention before the 6 th month (13,14) . It is important to consider that this study, as compared to others, covered a larger, more heterogeneous, population as concerns age and maybe this has influenced the results (15)(16)(17)(18)(19) .…”
Section: Discussionmentioning
confidence: 72%
“…Results show that the average age of suspicion, the first appointment with physician, diagnostic, intervention and adaptation of hearing aid occurred later than in other researches or standards determined by national and international committees, which recommend that the diagnosis occurs around the 3 rd and 4 th month of a baby's life, and the intervention before the 6 th month (13,14) . It is important to consider that this study, as compared to others, covered a larger, more heterogeneous, population as concerns age and maybe this has influenced the results (15)(16)(17)(18)(19) .…”
Section: Discussionmentioning
confidence: 72%
“…The most frequent risks found were similar to the ones found in the literature. Risk indicators associated with ICU stay 11 , use of ototoxic drugs 11,12,19,20 , congenital infection 11 , mechanical ventilation 11,12,19 and family history of hearing loss 11,20 were the most frequent risk indicators found in the literature.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have reported a greater rate of hearing loss in premature children 21 . Many studies have reported that birth weight below 1,500g is one of the most frequent indicators associating hearing disorders with children 6,12,20,30 . It is worth stressing the importance, not only of doing the NHS in premature babies, but also to follow up on their hearing and language development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The education in this context is an important tool in the actions of health promotion 9 . Faced with the need to increase knowledge on hearing health of health professionals, some studies 4,[10][11][12] have demonstrated the need for investment in the area of training, with regard to child's hearing health and issues involved with this subject.…”
mentioning
confidence: 99%